2011
DOI: 10.3174/ajnr.a2777
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Arteriovenous Shunting and Venous Congestion Identification in Dural Arteriovenous Fistulas Using Susceptibility-Weighted Imaging: Initial Experience

Abstract: SUMMARY:In this short report, we describe the potential contribution of SWI in the noninvasive evaluation of DAVFs. SWI images were compared with DSA for the identification of the location of the fistulous point, the presence of CVR, and the presence of the PPP. In 5 of 6 patients, it was possible to identify the fistulous locations depicted as hyperintensity within venous structures. Cortical venous reflux was underestimated on SWI in 3 cases of robust CVR and not identified in 2 cases of less severe CVR. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 27 publications
4
27
0
Order By: Relevance
“…The presence of these efferent pial venous drainage pathways carrying arterialized blood may impact upon the method and approach to treatment of these malformations, 12 and it is therefore important to differentiate them from veins enlarged because of passive venous congestion. These observations on the utility of SWI in differentiating between passive venous congestion and venous dilation from AVS in our series of patients are similar to the observations reported by Letourneau-Guillon and Krings 13 in their recent small series of patients with dural arteriovenous fistulas.…”
Section: Discussionsupporting
confidence: 79%
“…The presence of these efferent pial venous drainage pathways carrying arterialized blood may impact upon the method and approach to treatment of these malformations, 12 and it is therefore important to differentiate them from veins enlarged because of passive venous congestion. These observations on the utility of SWI in differentiating between passive venous congestion and venous dilation from AVS in our series of patients are similar to the observations reported by Letourneau-Guillon and Krings 13 in their recent small series of patients with dural arteriovenous fistulas.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, the combination of other MR imaging methods may help to differentiate this condition. Recent reports have suggested that some advanced MR imaging techniques such as dynamic susceptibility contrast (DSC) and susceptibility-weighted imaging (SWI) are capable of detecting and evaluating cortical venous reflux and venous congestion in patients with DAVF [25][26][27]. Further studies may be necessary to assess the value of the combination of ASL and other advanced MR imaging such as DSC and SWI for the demonstration of cortical venous reflux in DAVF.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, only local venous prominence on SWI was considered positive, and whole brain venous prominence was not judged positive. The ability of SWI to distinguish normal venous structures and abnormal congested veins should ideally be evaluated in a larger study including a control group of patients [18]. The final limitation is that hemodynamic loads by the thrombus and collaterals were not directly evaluated at the same time as SWI evaluation.…”
Section: Discussionmentioning
confidence: 99%